Increased aortic stiffness in prepubertal girls with Turner syndrome. Issue 1 (January 2017) - De Groote, Katya; Devos, Daniel; Van Herck, Koen; De Wolf, Daniel; Van der Straaten, Saskia; Rietzschel, Ernst; Raes, Ann; Vandekerckhove, Kristof; Panzer, Joseph; De Wilde, Hans; De Schepper, Jean
Abstract: Background: Aortic dilation and dissection contribute highly to the increased mortality of Turner syndrome (TS) but the exact pathophysiology is not completely understood. Design: Prospective case – control study. Methods: 15 prepubertal TS girls (median age 10.64, IQ 8.31–11.04) with a tricuspid (TAV, n = 9) or a bicuspid (BAV, n = 6) aortic valve, and 31 sex-, age-, and height-matched healthy controls underwent a cardiac and vascular ultrasound to evaluate aortic dimensions and elastic properties of the aortic wall. Results: TS BAV had significantly larger ascending aortic diameters than controls for absolute diameter, 22.2 ± 5.1 mm vs. 18.6 ± 1.9 mm ( p = 0.014) and z -score 1.7 ± 2.1 vs. 0.1 ± 0.7 ( p = 0.008). Distensibility of the ascending aorta was lower in the TS than in controls (40.2 × 10 −3 kPa −1, IQ 31.3–56.2 vs. 62.9 × 10 −3 kPa −1, IQ 55.5–76.5, p = 0.003), both for TS TAV ( p = 0.014) and BAV ( p = 0.005). Stiffness index was higher in TS than in controls (5.26, IQ 3.34–5.26 vs. 3.23, IQ 2.55–3.24, p = 0.005), both for TS TAV ( p = 0.028) and TS BAV ( p = 0.006). Pulse wave velocity was not different between groups. There was no correlation between stiffness and z -score of the ascending aortic diameter. Conclusions: In prepubertal TS girls, stiffness of the ascending aorta is increased in patients with a BAV and TAV while dilation of the ascending aorta is more frequent in BAV. This suggests an intrinsic aortic wall abnormality making all TS patients at increased risk for severe aortic complications although the risk is the highest for TS with BAV.